2018
DOI: 10.1038/s41598-018-19150-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Echo Time on IVIM Quantification of the Normal Prostate

Abstract: The two-compartment intravoxel incoherent motion (IVIM) theory assumes that the transverse relaxation time is the same in both compartments. However, blood and tissue have different T2 values, and echo time (TE) may thus have an effect on the quantitative parameters of IVIM. The purpose of this study was to investigate the effects of TE on IVIM-DWI-derived parameters of the prostate. In total, 17 healthy volunteers underwent two repeat examinations. IVIM-DWI data were scanned 6 times with variable TE values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Meanwhile, the results displayed that D * (90th) in PCa was significantly lower than that in BPH/prostatitis, while D * (kurtosis) in PCa was significantly higher than that in BPH/prostatitis, which is different from the results of Cui et al ( 28 ). Feng et al evaluated the effect of echo time value on IVIM quantification and showed that the accurate measurement of D * is still challengeable ( 33 ). D * is prone to errors, particularly when f gets very small ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the results displayed that D * (90th) in PCa was significantly lower than that in BPH/prostatitis, while D * (kurtosis) in PCa was significantly higher than that in BPH/prostatitis, which is different from the results of Cui et al ( 28 ). Feng et al evaluated the effect of echo time value on IVIM quantification and showed that the accurate measurement of D * is still challengeable ( 33 ). D * is prone to errors, particularly when f gets very small ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intravoxel incoherent motion parameters (especially D * ) have modest repeatability and reproducibility (Table 2), [121][122][123][124][125][126][127][128][129][130] perhaps due to their inherent inflexibility in the standard IVIM model and sensitivity to noise, 6 and several approaches have been explored to improve their uncertainty. IVIM values are dependent on the acquisition parameters such as b-values, 118 131 and fitting methods, 81 and uniform acquisition of IVIM data and development of robust IVIM fitting are warranted. Many efforts are underway to improve the estimation of IVIM parameters.…”
Section: Challengesmentioning
confidence: 99%
“…Tax et al investigated the TE dependency and diffusion‐T 2 spectra in the living human brain with 300 mT/m gradients of a Connectom scanner. Feng et al carried out multi‐b‐value and multi‐TE diffusion imaging on healthy human prostate to evaluate the influence of TE on reproducibility and quantification of IVIM diffusion model.…”
Section: Introductionmentioning
confidence: 99%